The Use of Deception in Selected Literary Texts: A Comparative Pragmatic Study - Kadhim Madhi, Zainab; Abbas Al-Zubaidy, Baidaa’ (International Journal of Psychosocial Rehabilitation, 2020)
Language plays a vital role in communicating and transmitting information between people, as well as in performing several other important functions, deception being one of them. The importance of this study in linguistics is related to the wide social use of deception and to the fact that it is one of the very important themes in literature. However, this field of research did not get what it deserved in research and study.This pragmatic study aims to explore the theatrical texts of the two historical periods (15th and 20th centuries) in English literature by comparing them to highlight how the authors of poetic theatrical texts use the pragmatic aspects of language, such as speech act theory, and how to override the Grice principle in order to achieve certain social goals.This study is designed to explore the linguistic features of deception in the Elizabethan era (Shakespeare’s Hamlet) and the twentieth century (Elliot’s Murder in the Cathedral) by comparing the deception methods used in both of them from the standpoint of the theory of pragmatics.The researcher hypothesized that the text of Hamlet uses deceptive language more than the text of Murder in the Cathedral. The second hypothesis is that Grice's cooperative principle is overridden in terms of the quality and the manner maxims more than the quantity and the relevance maxims in both plays.